Long-term consequences of agricultural policy decisions: How are forests planted under EEC regulation 2080/92 affecting biodiversity 20 years later?. (August 2019) - Vasconcelos, Sasha; Pina, Sílvia; Reino, Luís; Beja, Pedro; Moreira, Francisco; Sánchez-Oliver, Juan S.; Catry, Inês; Faria, João; Rotenberry, John T.; Santana, Joana
Abstract: Large-scale afforestation of agricultural land was carried out in the 1990s under the Common Agricultural Policy of the European Union. This policy aimed at delivering environmental benefits, among them positive biodiversity effects. However, knowledge of the long-term biodiversity impacts of these afforestation schemes remains very limited, particularly for insects. We provide a case study examining the biodiversity impacts of afforestation carried out in Mediterranean grasslands in southern Portugal. We sampled orthopterans and butterflies in native oak and pine plantations established under EEC regulation 2080/92, and in older exotic eucalyptus plantations. Sampling was also conducted in grassland habitats (permanent pastures and fallow land) adjacent to each plantation, and at plantation-grassland edges. In general, plantations supported lower orthopteran species richness and fewer orthopterans of conservation value than grassland and edges, particularly for eucalyptus plantations. Conversely, plantations were of higher conservation value for butterflies, and edges supported the highest butterfly richness. Plantations hosted some orthopteran and butterfly species that did not occur in grasslands, and so contributed to increase species richness at the landscape scale. Overall, results underline the importance of grassland, especially for orthopterans, and show that native plantations and associated edges can also provide habitat for species of conservation value. Therefore, retaining large grassland tracts and planting native rather than exotic tree species might minimize the negative effects of plantations for insect biodiversity in Mediterranean grassland. Overall, findings show that agricultural policy decisions can have protracted implications for biodiversity, thereby requiring long term environmental assessments and monitoring.